Reliability and Validity of the Physical Activity Questionnaire for Older Children (PAQ-C) In Malay Language - Nor Azian Mohd Zaki; Norhafizah Sahril; Mohd Azahadi Omar; Muhammad Hasnan Ahmad; Azli Baharudin; Noor Safiza Mohd Nor (Universiti Kebangsaan Malaysia, 2016)
Introduction: Physical activity assessment in children is the first step in assessing the relationship between activity and health, as well as the determinants of childhood physical activity and changes in activity level.Physical Activity Questionnaire for Older Children (PAQ-C) is self- administered questionnaire to assess physical activity among older children. The objective of this study was to determine the validity and reliability of Physical Activity Questionnaire for Older Children in Malay language PAQ-C (M). Methods: The validation study was done among 73 students aged 10 to 17 years old. The PAQ-C was translated into Malay language using forward and backward translation. The evaluation of the psychometric properties included internal consistency, test-retest reliability and criterion validity. Reliability of PAQ-C (M) was determined using Cronbach alpha and intra-class correlation coefficient (ICC). The PAQ-C (M) was administered twice in one week interval to assess test-retest reliability. Criterion validity was assessed between PAQ-C (M) and 3 Day Physical Activity Recall (3DPAR). Results: The internal consistency of PAQ-C (M) assessment calculated in this study was α = 0.75 and α = 0.77 for assessments one and two, respectively. The ICC between individual items of PAQ-C (M) was 0.59 to 0.91, indicating moderate to good correlation. The Spearmen correlation coefficient between PAQ-C (M) and 3DPARwas acceptable (r=0.60, p<0.01). Conclusions: In conclusion, the findings of this study suggest that the PAQ-C (M) has moderate to good reliability and validity in assessing physical activity among older children and adolescents. Future validation of PAQ-C (M) against different measures such as accelerometer is recommended.